-33+(-7)=29

Simple and best practice solution for -33+(-7)=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33+(-7)=29 equation:


Simplifying
-33 + (-7) = 29
-33 + -7 = 29

Combine like terms: -33 + -7 = -40
-40 = 29

Solving
-40 = 29

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 14y-4=3y | | 2x^2+(3x-5)=37 | | (3x^4+4x^3-5)-(8x^2-5x+8)= | | x-7y-14=0 | | x+2y=-13 | | 176=H+(219) | | (2x^2)=(3x^2-64) | | y=6x+b | | b=y-6x | | 2x+y=-14 | | 3+(4z+5)=31 | | 30x^2+27x= | | x/6-4=x/6 | | abs(2x-3)=4 | | 6x+17=4x+9 | | 9(x+2)=81(x+1) | | 4y^2-1=15 | | -2(3x-2)+X+9X=-3 | | -16x^2+400=0 | | 3y=81 | | cos(x)*cosh(x)=1 | | 2x^2+9x+2= | | 2000+Y=9500 | | -x^2-3x+3=0 | | 3x*x+27x=0 | | 3x*x+27=0 | | 3c^2=-16c+5 | | n+40=11q+9 | | 2m+3=7 | | 4(m+2)=40 | | 3x^3+25x^2+8x=0 | | g/2+3=15 |

Equations solver categories